Perlindungan Hukum Konsumen E-Commerce pada Produk Kesehatan: Pembelajaran pada Kejahatan Siber - Laksana, Tri Ginanjar (Indo Green Journal, 2024)
e-commerce is a quickly expanding industry in the more sophisticated digital age, particularly in the market for health products. More individuals are doing so because purchasing health items online is so convenient. However, as technology develops, so does the possibility of cybercrime, which puts online shoppers in danger. Legal protection is thus crucial to safeguarding customers throughout their online transactions. Finding out and discussing the legal protections afforded to online shoppers of health products—lessons learned from cybercrime—is the goal of this study. Normative legal research techniques (normative juridical) and empirical legal research methods (empirical juridical) are the research approaches employed to address the issues in this study. Primary and secondary data are the two categories of data employed in this descriptive-analytical study. Based on the study findings, it can be said that customers may trade online confidently and without fear of becoming victims of cybercrime if they have legal protection. In order to safeguard customers and maintain the safety and reliability of the health product market, governments and e-commerce companies must collaborate. As a result, online shoppers may complete their purchases without concern about fraud or cybercrime, giving them peace of mind.